Survivors’ Beliefs About the Causes of Sexual Offending: An Australian Study - Richards, Kelly (Violence against women, 2022)
Policies designed to prevent sexual (re)offending are often proposed on behalf of survivors of sexual violence. However, no research has examined survivors’ beliefs about the causes of sexual offending. This is a critical gap, because how individuals understand the causes of sexual offending has long been thought to inform their support for particular policy responses. This article presents findings from the first study to specifically examine survivors’ views about the causes of sexual offending, based on interviews with 33 survivors from Australia. It demonstrates that survivors’ beliefs are highly complex and multifaceted, and destabilizes the uniform survivor of governmental imagination.